Ammonia-induced mitochondrial dysfunction and energy metabolism disturbances in isolated brain and liver mitochondria, and the effect of taurine administration: relevance to hepatic encephalopathy treatment - Niknahad, Hossein (Clin Exp Hepatol, 2017)
INTRODUCTION: Ammonia-induced oxidative stress, mitochondrial dysfunction, and energy crisis are known as some the major mechanisms of brain injury in hepatic encephalopathy (HE). Hyperammonemia also affects the liver and hepatocytes. Therefore, targeting mitochondria seems to be a therapeutic point of intervention in the treatment of HE. Taurine is an abundant amino acid in the human body. Several biological functions including the mitochondrial protective properties are attributed to this amino acid. The aim of this study is to evaluate the effect of taurine administration on ammonia-induced mitochondrial dysfunction. MATERIAL AND METHODS: Isolated mice liver and brain mitochondria were exposed to different concentrations of ammonia (1, 5, 10, and 20 mM) and taurine (1, 5, and 10 mM), and several mitochondrial indices were assessed. RESULTS: It was found that ammonia inhibited mitochondrial dehydrogenases activity caused collapse of mitochondrial membrane potential (MMP), induced mitochondrial swelling (MPP), and increased reactive oxygen species (ROS) in isolated liver and brain mitochondria. Furthermore, a significant amount of lipid peroxidation (LPO), along with glutathione (GSH) and ATP depletion, was detected in ammonia exposed mitochondria. Taurine administration (5 and 10 mM) mitigated ammonia-induced mitochondrial dysfunction. CONCLUSIONS: The current investigation demonstrates that taurine is instrumental in preserving brain and liver mitochondrial function in a hyperammonemic environment. The data suggest taurine as a potential protective agent with a therapeutic capability against hepatic encephalopathy and hyperammonemia.